2020
DOI: 10.3390/ani10081423
|View full text |Cite
|
Sign up to set email alerts
|

Mirtazapine Reduces Adipocyte Hypertrophy and Increases Glucose Transporter Expression in Obese Mice

Abstract: Metabolic syndrome is known to engender type 2 diabetes as well as some cardiac, cerebrovascular, and kidney diseases. Mirtazapine—an atypical second-generation antipsychotic drug with less severe side effects than atypical first-generation antipsychotics—may have positive effects on blood glucose levels and obesity. In our executed study, we treated male high-fat diet (HFD)-fed C57BL/6J mice with mirtazapine (10 mg/kg/day mirtazapine) for 4 weeks to understand its antiobesity effects. We noted these mice to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(63 citation statements)
references
References 61 publications
3
59
0
1
Order By: Relevance
“…Moreover, the increase in number of large adipocytes due to risperidone treatment may be attributable to the ability of chronic risperidone treatment to suppress energy expenditure through reductions in total resting metabolic rate and nonaerobic metabolism in mice [ 39 ]. Another explanation for this result is risperidone’s promotion of fat adipogenesis, which accords with reported findings that risperidone can increase or activate adipogenic marker gene expression—such as through protein kinases A and C-β, tumor growth factor-β, extracellular signal-related kinase (ERK) 1/2, or hormone-sensitive lipase expression—which in turn influences lipogenesis and HFD-induced adipocyte hypertrophy [ 25 , 40 , 41 , 42 ]. Moreover, the synthesis of leptin, a food intake regulation hormone produced in hypothalamus, predominantly occurs in white adipose tissue (WAT) [ 24 ].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Moreover, the increase in number of large adipocytes due to risperidone treatment may be attributable to the ability of chronic risperidone treatment to suppress energy expenditure through reductions in total resting metabolic rate and nonaerobic metabolism in mice [ 39 ]. Another explanation for this result is risperidone’s promotion of fat adipogenesis, which accords with reported findings that risperidone can increase or activate adipogenic marker gene expression—such as through protein kinases A and C-β, tumor growth factor-β, extracellular signal-related kinase (ERK) 1/2, or hormone-sensitive lipase expression—which in turn influences lipogenesis and HFD-induced adipocyte hypertrophy [ 25 , 40 , 41 , 42 ]. Moreover, the synthesis of leptin, a food intake regulation hormone produced in hypothalamus, predominantly occurs in white adipose tissue (WAT) [ 24 ].…”
Section: Discussionsupporting
confidence: 84%
“…The serum and hepatic triglyceride levels were 27% ( Figure 5 a) and 28% ( Figure 5 b) in the treated mice than in the control mice. Fatty acid synthase (FASN) is a crucial liver enzyme for lipid homeostasis and triglyceride synthesis [ 23 ], whereas patatin-like phospholipid domain containing protein 3 (PNPLA3) is a pathologic marker for lipogenesis regulation in obesity, nonalcoholic fatty liver disease, and cardiovascular disease [ 25 ]. Western blot analysis ( Figure 5 c) indicated that hepatic FASN and PNPLA3 expression was 42% ( Figure 5 d) and 17% ( Figure 5 e) higher in the treated mice than in the control mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations